2016
DOI: 10.1016/j.jbiotec.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A rapid solubility-optimized screening procedure for recombinant subtilisins in E. coli

Abstract: Subtilisins and other serine proteases are extensively used in the detergent, leather and food industry, and frequently under non-physiological conditions. New proteases with improved performance at extreme temperatures and in the presence of chemical additives may have great economical potential. The increasing availability of genetic sequences from different environments makes homology-based screening an attractive strategy for discovery of new proteases. A prerequisite for large-scale screening of protease-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 46 publications
0
54
0
Order By: Relevance
“…To facilitate enzyme expression we used our previously developed screening procedure for subtilisin‐like serine proteases . The Planococcus sp.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To facilitate enzyme expression we used our previously developed screening procedure for subtilisin‐like serine proteases . The Planococcus sp.…”
Section: Methodsmentioning
confidence: 99%
“…The isp gene was sub‐cloned from the delivery vector to a suite of expression vectors using a fragment exchange (FX) cloning method . Construction of the expression vectors have been described previously …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Subtilisin E is typically obtained in inclusion body and purified through a complicated renaturation process [23-25] and the highest yield was estimated to be 40-50 mg/liter of culture[26]. Recently, Gro Elin et al overcame this problem by fusing maltose-binding protein (MBP) or the small ubiquitin-related modifier (SUMO) to Subtilisins[27]. But we found that SES7 is soluble without such modifications (Figure S2).…”
Section: Resultsmentioning
confidence: 99%